COVID‐19‐Related Facilitators and Barriers to In‐Person Learning for Children With Intellectual and Development Disabilities. (20th November 2022) - Vestal, Liz E.; Schmidt, Ann M.; Dougherty, Nikole L.; Sherby, Michael R.; Newland, Jason G; Mueller, Nancy B.
ABSTRACT: BACKGROUND: Schools provide essential functions for children with intellectual and developmental disabilities (IDD), but their vulnerability to infection with SARS‐CoV‐2 are a barrier to in‐person learning. This qualitative study aimed to understand how weekly SARS‐CoV‐2 screening testing of students and staff could best facilitate in‐school learning during the pandemic. METHODS: Thirty‐one focus groups were held with school staff and parents of children with IDD to examine the perceptions of COVID‐19 during the 2020‐2021 school year. Responses were analyzed using a directed thematic content analysis approach. RESULTS: Five principal themes were identified: risks of returning to in‐person learning; facilitators and barriers to participation in SARS‐CoV‐2 screening testing; messaging strategies; and preferred messengers. IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: Staff and families agreed that saliva‐based SARS‐CoV‐2 screening testing helps increase comfort with in‐person learning. Screening testing increased family and school staff comfort with in‐person learning particularly because many students with special needs cannot adhere to public health guidelines. CONCLUSION: To keep children with IDD in school during the pandemic, families found SARS‐CoV‐2 screening testing important, particularly for students that cannot adhere to mitigation guidelines.